Frequent peer problems in Australian children and adolescents. Issue 3 (11th July 2016) - Denham, Renee; McGee, Tara Renae; Eriksson, Li; McGrath, John; Norman, Rosana; Sawyer, Michael; Scott, James
Abstract : Purpose: – Whilst overt bullying has received considerable attention for its negative impact on the emotional well-being of children and adolescents, peer problems such as excessive teasing and social exclusion have received less consideration. The purpose of this paper is to examine the prevalence, demographic, and clinical correlates of frequent peer problems in children and adolescents who participated in the Australian National Survey of Mental Health and Well-Being. Design/methodology/approach: – Participants were a nationally representative sample of 2, 107 children (aged 6-12 years), and 1, 490 adolescents (aged 13-17 years). Frequent peer problems (excessive teasing or social exclusion) were measured by parental report for children, and self and parental report for adolescents. Associations with a number of mental health problems were examined, including being in the clinical range for internalising and externalising symptoms, having major depressive disorder, attention deficit hyperactivity disorder or conduct disorder, low self-esteem, experiencing suicidal ideation and behaviour, or using marijuana and alcohol. Findings: – One in 30 children and one in 20 adolescents experienced frequent peer problems. Parents less commonly identified frequent peer problems than were self-reported by their adolescent children. Frequent peer problems were strongly associated with all mental health problems except alcohol and marijuana use. Originality/value: – Frequent peer problems are associated with a greatly increased risk of mental health problems. Identifying those children and adolescents with frequent peer problems provides opportunity for assessment and intervention of emotional and behavioural problems.